A novel and clean utilization of converter sludge by co-reduction roasting with high-phosphorus iron ore to produce powdery reduced iron. (20th August 2022) - Wu, Shichao; Sun, Tichang; Kou, Jue
Abstract: The efficient and harmless utilization of converter sludge (CS) still faces problems. In the traditional roasting process of high-phosphorus iron ore (HPIO), a large amount of sodium or calcium salt needs to be added to enhance iron recovery and dephosphorization, which leads to an increase in production costs. In this paper, the co-reduction roasting followed by magnetic separation process was designed to realize the full recycling and clean utilization of CS and upgrade HPIO. The results show that the hazardous CS can serve as an ideal admixture in this process which ameliorated the conversion of iron oxides to metallic iron and inhibited the reduction of phosphorus in iron oxides in HPIO. And the element of iron in CS was fully recycled as well. Under optimal conditions, the powdery reduced iron with 93.45% Fe and 0.09% P was produced, which can be a superior substitute for scrap steel in steelmaking, and the iron recovery reached 96.10%. The tailings were cleaned with a leaching toxicity significantly lower than the standard threshold, and the composition indicate that they were excellent raw material for cement production. This novel process realizes the comprehensive and green utilization of CS. Graphical abstract: Image 1 Highlights: CS is a hazardous solid waste with heavy metals and HPIO is a refractory iron ore. Synergetic use of CS-HPIO was realized by co-reduction roasting and magnetic separation. CS acts as an additive to promote reduction of iron oxides and dephosphorization. Powdery reduced iron was produced as a superior material for steelmaking. Tailings were harmless and could be a promising raw material to produce cement.